Oral Tongue Malignancies in Autoimmune Polyendocrine Syndrome Type 1 - Bruserud, Øyvind; Costea, Daniela-Elena; Laakso, Saila; Garty, Ben-Zion; Mathisen, Eirik; Mäkitie, Antti; Mäkitie, Outi; Husebye, Eystein S. (Frontiers in Endocrinology, 2018)
Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) or Autoimmune polyendocrine syndrome type-1 (APS-1) (APECED, OMIM 240300) is a rare, childhood onset, monogenic disease caused by mutations in the Autoimmune Regulator (AIRE) gene. The overall mortality is increased compared to the general population and a major cause of death includes malignant diseases, especially oral and esophageal cancers. We here present a case series of four APS-1 patients with oral tongue cancers, an entity not described in detail previously. Scrutiny of history and clinical phenotypes indicate that chronic mucocutaneous candidiasis and smoking are significant risk factors. Preventive measures and early diagnosis are important in order to successfully manage this potentially fatal disease.